Impact of improved stroke green channel process on the delay of intravenous thrombolysis in patients with acute cerebral infarction during the COVID-19 pandemic: An observational study - Wang, Qiwei; Wang, Yan; Wang, Yongpeng; Bi, Qianqian; Zhang, Quanbin; Wang, Feng (Frontiers in Neurology, 2022)
Objective: This study analyzed the impact of the improved stroke green channel process on the delay of intravenous thrombolysis in patients with acute cerebral infarction under coronavirus disease 2019 (COVID-19) prevention and control measures. Methods: We included 28 patients from the stroke center of the Seventh People’s Hospital of Shanghai University of Traditional Chinese Medicine before the improvement of the stroke green channel process (March¬–May 2019), as well as 59 patients during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak (March–May 2020) and 39 patients during the Omicron variant outbreak (March–May 2022) after the improvement of stroke green channel process. The onset-to-door time (ODT), door-to-needle time (DNT), door-to-imaging time (DIT), and door-to-test completion time were compared among the three groups. We analyzed the impact of this process improvement in the emergency green channel during the pandemic on the delay of intravenous thrombolysis. Conclusion: During the two periods of the COVID-19 outbreak (SARS-CoV-2 and Omicron), after the improvement of the green channel for intravenous thrombolysis, there might be some delay in in-hospital DIT during the SARS-CoV-2 outbreak, however, the pre-hospital delay indicator ODT and in-hospital delay indicator DNT for intravenous thrombolysis were not affected.